FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BEI - Mohammad Eddy Rosyadi; Ester Lusiana (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to obtain the empirical evidence about factors which influence dividend policy. The independent variables in this research are profitability, liquidity, growth, firm risk, market to book value, free cash flows, leverage, ownership structure and firm size, with dividend payout ratio as the dependent variable. The population of this research is non financial companies which listed in the Indonesia Stock Exchange from 2012 until 2014. The samping technique used in this research is purposive sampling. The sample consists of 89 non financial companies. This research uses multiple regression as the statisctial analysis method. The data type is secondary data consists of annual financial statements collected from IDX website. The results of this research show that profitability, firm risk, market to book value, and ownership structure have influence toward dividend payout ratio. Whereas, liquidity, growth, free cash flows, leverage, and firm size have no influence toward dividend policy